Use of Patient Preference Studies in HTA Decision Making: A NICE Perspective - Bouvy, Jacoline C.; Cowie, Luke; Lovett, Rosemary; Morrison, Deborah; Livingstone, Heidi; Crabb, Nick (The patient : patient-centered outcomes research, 2020)
Patient preference studies could provide valuable insights to a National Institute for Health and Care Excellence committee into the preferences patients have for different treatment options, especially if the study sample is representative of the broader patient population. We identify three main uses of patient preference studies along a technology’s pathway from drug development to clinical use: in early clinical development to guide the selection of appropriate endpoints, to inform benefit-risk assessments carried out by regulators and to inform reimbursement decisions made by health technology assessment bodies. In the context of the National Institute for Health and Care Excellence’s methods and processes, we do not see a role for quantitative patient preference data to be directly incorporated into health economic modelling. Rather, we see a role for patient preference studies to be submitted alongside other types of evidence. Examples where patient preference studies might have added value in health technology assessments include cases where two distinctly different treatment options are being compared, when patients have to decide between multiple treatment options, when technologies have important non-health benefits or when a treatment is indicated for a heterogenous population.